Repetitive ventricular tachycardia in a syncopal child: Cause or incidental finding ? - Massin, Martial (Ann Noninvasive Electrocardiol, 2017)
A 15‐year‐old girl suffered recurrent syncopal episodes during 7 years. Events were precipitated by exercise or emotional stress, leading to the diagnosis of reflex syncope. Exercise testing induced recurrent salvos of nonsustained right ventricular outflow tract tachycardia. This arrhythmia is often asymptomatic, reflex syncope is very frequent and both causes are related to the same triggering situations. It was therefore essential to obtain recordings during syncopal events and to observe the clinical evolution under effective treatment in order to make the right diagnosis.